PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG DI MANOKWARI - Suliatin, Titik; Bajari, Makarius; Lotte, Natalia Anastasia (Lensa Ekonomi, 2024)
This study aims to examine and analyze the effect of product quality and price on samsung smartphone purchasing decisions in West Manokwari District. The type of research used is a quantitative approach with an associative type of problem. The population in this study was people in West Manokwari District who used Samsung smartphones and had used Samsung smartphones for at least 1 year. The sample collection technique is non probability sampling with a total sample of 100 respondents. The primary data used is by conducting interviews and distributing questionnaires. Secondary data is obtained from journals, books, websites, catalogs, and data of Samsung smartphone users in Manokwari. The results of this study show that the product quality variable partially affects samsung smartphone purchase decisions, and subsequent test results show that price variables have a partial effect on Samsung smartphone purchase decisions. As well as showing that the variables of product quality and price have a simultaneous effect on Samsung's smartphone purchase decision, meaning that the quality of the product provided is good and the price offered is appropriate and competitive can improve samsung's smartphone purchase decision in West Manokwari District.